Community development practices in Tanzania: Issues and challenges - Ndiege, Bernard P. (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales, 2019)
The history of community development in mainland Tanzania can be traced back just after the Second World War. From this time, more improvement has been made, even after independence (1961). Activities which are carried out originated from the communities themselves. In this respect, community development workers do their best to identify local available resources in collaboration with community members (community participation) to ensure sustainability of different projects throughout the country. Current challenges in a context of a wide variety of cults and cultures include training competent workers, adopting a national approach and conducting more in-depth research.